"Having Students is Entirely Necessary": Tutors' feedback of experiential learning in an MPharm programme (TELL Project). (March 2023) - Jacob, Sabrina Anne; Boyter, Anne C.
Abstract: There is an increased reliance on experiential learning tutors and placement sites, and as such there is a need to determine tutors' perceptions about experiential learning as well as identify their needs. A mixed-methods study was undertaken involving tutors in hospitals and community pharmacies. There were 58 responses to the online survey. Five focus groups consisting of 25 hospital tutors, and 11 one-on-one interviews with community tutors were conducted. Experience as a tutor was dependant on students' attitudes and engagement, with poor attitude highlighted as a challenge. Limited time and placement duration were also identified as challenges, while a benefit noted was opportunities for staff recruitment. There was good support for students being sent to primary care for placements. Programme improvement is needed, involving both tutors and students in the co-design of EL to address gaps and avoid future dissatisfaction as well as ignite a sense of ownership by all parties. Highlights: Experiential learning tutors act as a bridge between academia and practice. Experience as a tutor was dependent on students' engagement and attitudes. EL afforded an opportunity for future staff engagement. Lack of time and limited EL duration are major barriers to engagement with students Support for students undertaking EL in primary care sites.